2018
DOI: 10.2174/1573396313666170216120230
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Changes in Neonates in the First 72 Hours of Birth: An Observational Study

Abstract: We confirm the variation in cutaneous lesions and their time of onset in neonates. Transient and physiological changes are more frequent and disappeared spontaneously. Number of lesions/neonate was more in premature babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, the authors reported that the most significant risk factor for developing the condition was found to be being a preterm infant (birth weight <2500 g). 9,10 Further epidemiological data show that the condition is not usually confined to a certain race. However, evidence indicates that the condition is more common among males.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Furthermore, the authors reported that the most significant risk factor for developing the condition was found to be being a preterm infant (birth weight <2500 g). 9,10 Further epidemiological data show that the condition is not usually confined to a certain race. However, evidence indicates that the condition is more common among males.…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…With these limitations, when a child is admitted in an ICU and exposed to disinfectants, adhesives, heat, probes, needles, electrodes and also frequent handling, the skin becomes more prone to develop injury. 2,3,4,5 Not many studies exist on the profile of iatrogenic skin injury in the neonatal ICU. With increasing number of institutional deliveries, more and more children are getting admitted to neonatal ICU and keeping this in mind, we decided to undertake a study on the clinical profile of iatrogenic skin injuries in neonatal ICU with specific reference to the causative agents or mechanisms.…”
Section: Introductionmentioning
confidence: 99%